Patient's right to protection of personal data in the legal system of Bosnia and Herzegovina - Bevanda, Marko (Medicine, law & society, 2017)
Health-related personal data belong to a category of sensitive data which, therefore, must be specially protected. The protection of personal health data is one of the patients' fundamental rights. Doctors protect their patients' interests only when the information gained about patients, while providing them medical treatment, are kept secret. In this paper, the authors provide an overview of the legal framework for the protection of health-related personal data in the legal system of Bosnia and Herzegovina. In addition to the analysis of the relevant legal provisions and considering the situation in practice, it can be concluded that formal harmonisation of legislation with the acquis communautaire in this field is not followed by effective implementation of regulation in practice.
Keywords: doctor; liability for damage; medical malpractice; privacy